INTERPRETING THE RESULTS OF RANDOMIZED CONTROLLED TRIALS - Nikolić, Božana (HEALTH CARE, 2023)
The aim of this review article is to explain, with the help of examples, how to choose, calculate and interpret effect measures in randomized controlled trials. Randomized controlled trials (RCTs) belong to the group of experimental studies and they are conducted on sick persons. In these studies, participants are assigned to the experimental group, which receives the medicine which is being tested, and to the control group, which receives a placebo or a medicine, which has been previously used. The results of RCTs can be presented through relative or absolute effect measures. Relative effect measures include the relative risk (RR) and the relative risk reduction (RRR), while absolute effect measures include the absolute risk reduction (ARR) and the number of patients who should be treated (Number Needed to Treat – NNT). The strongest evidence of cause and effect is obtained in these studies, but these studies are rarely conducted because of their cost. The small number of participants in these studies can be overcome by using meta-analysis and multicenter studies.
Keywords: epidemiological studies, randomized controled trial, effect measures